2022-RA-594-ESGO Application of ultrasound in cervical cancer (a case report and updated literature review). (20th October 2022) - Djokovic, Dusan; Telhado, Conceição; Pereira, José Silva; Conde, Pedro
Abstract : Introduction/Background: Technological development and specialized training of operators have led to the increasing usefulness of ultrasonography (US) in patients with cervical cancer (CC). Most women with squamous cell CC (SCC) present hypoechoic lesions and increased vascularity, while rare-type CC are commonly isoechoic. This communication presents a case of SCC with less frequent US characteristics and summarizes updated information on the role of US in CC. Methodology: Case report and non-systematic literature review (MEDLINE, 2012 – 2022). Results: A 38-year-old nulliparous woman, with an irrelevant medical history, no desire to procreate, never involved in the immunization and CC screening programs by personal decision, was admitted to our department due to intense acute genital hemorrhage. Physical examination revealed a bleeding nodular lesion, apparently protruding from the cervical canal. Bleeding was controlled by tamponade. Transrectal US indicated an anterior cervical isoechoic lesion (34 x 21 x 30 mm), with an ovoid shape, regular edges and lateral acoustic shadows (see accompanying images). Although these were not the most common US characteristics of CC, the Doppler study (color score 3) raised suspicion. No signs of parametrial affectation were observed. Colposcopy with biopsy was performed (histological diagnosis: non-keratinizing SCC). Pretreatment gynecological US and magnetic resonance imaging (MRI) provided concordant information while thoraco-abdominal computerized tomography did not evidence secondary lesions (T1b1N0M0). The patient underwent radical hysterectomy (type C), bilateral salpingectomy, bilateral pelvic lymph node dissection and ovarian transposition. In accordance with the literature: transvaginal/transrectal expert US provides highly accurate information on detecting CC, being a convenient and cost-effective modality for assessing local extension (accuracy similar to that of MRI). Doppler studies may be useful for evaluating responses to various treatments. US guidance may be helpful in the delivery of intracavitary brachytherapy. Conclusion: Expert US provides valuable information for detecting invasive CC and assessing the local tumor spread.